An Innovative Interprofessional Assessment - Strudwick, Ruth; Harvey-Lloyd, Jane (International Journal of Practice-based Learning in Health and Social Care, 2016)
This article describes and evaluates the assessment used for a UK-based module entitled IPL - Working with Others. The module was attended by 320 students from adult nursing, child health nursing, mental health nursing, midwifery, social work, operating department practice, diagnostic radiography and therapeutic radiography. Students were divided into interprofessional groups of eight students. The groups were given a case study of a service user coming into contact with different health and social care professionals. They had to work together to produce a poster, based on the case study. The interprofessional groups provided a ‘real’ experience of working together and understanding one another’s roles. The students then had to defend their poster as a group and respond to questions from two assessors. In order to review the assessment, both students and staff were asked to provide feedback about the assessment process, listing the positive and challenging aspects. All of the staff provided feedback (12), and 192 (60%) students also provided feedback. It was found that the assessment worked well, both staff and students having found it to be both a good learning experience as well as being a good way to assess IPL. Students had a ‘real’ experience of interprofessional working, facing barriers and challenges to overcome which are similar to those in practice.